GOOD GOVERNANCE TO VILLAGE GOVERNMENT PERFORMANCE MODERATED COMPETENCY APPARATUS COMMITMENT FINANCIAL MANAGEMENT JUMANTONO KARANGANYAR - Setyaningsih SU, Setyaningsih SU; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to analyze the effect of good governance on village government performance moderated by competence, apparatus commitment, financial governance in the village government of Jumantono sub-district, Karanganyar regency. The population in this study were all Village Governments in 11 Villages, Jumantono District, Karanganyar Regency with a total of 135 people. This study uses census research by taking the entire population as respondents. The data analysis technique used multiple linear regression analysis and absolute difference test. Hypothesis testing using t test. The results showed (1) Good governance, competence, apparatus commitment, and financial governance have a significant effect on the performance of the village government in Jumantono District, Karanganyar Regency.